Recyclable Nanocrystalline Copper Based on MoO3/SiO2 as an Efficient Catalyst for Acylation of Amines - Sharda P. Dagade; Jaymala M. Deshmukh (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2019)
Various loadings of copper supported on MoO3/SiO2 (CMS) were prepared by sol-gel method and used for the synthesis of substituted benzimidazole. Further it was characterized by using X‐ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Energy Dispersive X-ray (EDX), Transmission Electron Microscopy (TEM), and acidity measurement by potentiometric method. XRD results indicated that Cu is present on the support primarily as CuO. The SEM and TEM results showed dispersion of cubic CuO nanoparticles on the surface. These mixed oxides were studied for the acylation of o-phenylene diamine with acetic acid in liquid phase. 10 wt. % CMS gave best results at 110 ºC with 94.81 % conversion of o-phenylene diamine and 100 % selectivity of substituted benzimidazole. Different parameters were studied for optimization of acylation, such as: temperature, acylating agents, solvents, amount of catalyst, and different catalysts. The CMS catalyst could also be recovered and reused at three times without any discernible decrease in its catalytic activity.